مدى مساهمة نظم المعلومات المحاسبية في الرفع من كفاءة الأداء المالي (دراسة ميدانية على شركة ليبيانا) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The purpose of this study is to explore the concepts of  accounting information systems and financial performance. Also, to knowing the role of accounting information systems in improving financial performance in order to fighting this phenomenon and limit it through a field study by surveying the views of Employees in Libyana company  in Tripoli . In order to achieve the objectives of the study, the descriptive analytical approach was adopted. (62) questionnaires had been distributed to the study community, while (53) of them were collected back, and the SPSS program was used to analyze the responses of the sample members. This study reached a number of results, the most important of which is there are no future planning by high management to improve accounting information systems in the Libyana company .Based on this finding, the study recommends that, high management must be provide future plans to improve their accounting information systems.
Keywords: Accounting information Systems; Financial performance; Libyana company